Islamic Employer Branding and Social Media Engagement for Attracting Generation Z Talent - Agus Supriyanto (Edupedia Publisher, 2025)
Purpose – The digital transformation era has reshaped recruitment practices, requiring organizations to develop innovative employer branding strategies to attract Generation Z talent. This study aims to explore how Islamic values-based employer branding communicated through social media influences the attractiveness of organizations among Muslim Generation Z job seekers. Methodology – This study employed a descriptive phenomenological qualitative design using a multi-case study approach. Data were collected from three Islamic-oriented digital companies and creative technology agencies in Indonesia. Purposive sampling was used to select 35 participants, consisting of 15 HR practitioners and digital business owners, as well as 20 Muslim Generation Z job seekers. Data were gathered through in-depth semi-structured interviews and analyzed using thematic analysis involving data reduction, coding, categorization, and interpretation. Findings – The findings reveal that Islamic employer branding effectively enhances organizational attractiveness when communicated through social media platforms such as Instagram Reels and TikTok. Core Islamic values, including amanah (integrity and accountability), 'adl (fairness and equitable compensation), itqan (professional excellence), and hifz al-nafs (mental and spiritual well-being), emerged as key dimensions influencing Generation Z’s employment preferences. Transparent and authentic digital narratives strengthened employer value propositions and reduced concerns regarding toxic workplace cultures and exploitation in the digital industry. These findings suggest that integrating Islamic ethical principles into employer branding can improve talent acquisition outcomes among Muslim Generation Z. Novelty – This study extends the Islamic Human Resource Management literature by proposing a social media-driven Islamic employer branding framework tailored to Generation Z talent attraction. Significance – The findings provide practical guidance for HR professionals, digital entrepreneurs, and organizations seeking to design value-based recruitment strategies in the digital labor market.